Factors Determining Poverty Rate in Sulawesi and Maluku in 2010-2019 - Mohamad Ahlis Djirimu (Fakultas Ekonomi, Universitas Bangka Belitung, 2023)
This study aimed to determine the effect of economic growth, education level, health status, and inflation on Sulawesi and Maluku Islands' poverty in the 2010-2019 period. Data were analyzed using the panel data regression with the Random Effect Model (REM). The results indicated that economic growth positively and significantly affected the poverty rate, while the average length of schooling and life expectancy had a negative and significant impact. Conversely, inflation negatively but insignificantly affected poverty in Sulawesi and Maluku Islands.